Feasibility Analysis of Egg-Laying Chicken Business Performance in Donggala Regency (Case Study of CV. Taufik Nur) - Muhamad; Guasmin; Burhanuddin (Universitas Muhammadiyah Palu, 2025)
This study aims to determine the financing analysis and feasibility of the performance of a laying hen farm in Donggala Regency. This research is a case study on the laying hen farm business of CV. Taufik Nur located in Donggala Regency. The determination of the research location was done intentionally (purposive), with the consideration that CV. Taufik Nur is one of the laying hen farm businesses that has been running its business for quite a long time in Donggala Regency. Primary data collection was obtained through observation and interviews with the management of CV Taufik Nur, while secondary data was obtained from related agencies and literature relevant to the purpose of this study. The results of the study indicate that the company has a fairly high liquidity ratio, above the industry average standard. The results of the average Leverage ratio calculation are very small compared to the amount of working capital owned, in other words, the amount of company debt provides a small contribution to the value of the company's equity. The Activity ratio value obtained from the turnover of raw materials is quite smooth where the company uses layer chickens for 1.5 years to 2.5 years before being culled. The profitability ratio analysis shows that the company's condition is generally good, as evidenced by the Gross Profit Margin and Net Profit Margin ratios, which are above the industry average. Furthermore, the operating expenses ratio is generally low, at below 35%. However, the ROI ratio obtained shows that the return on investment is below the industry average of 30%.